Diagnosis and management of Pneumocystis jirovecii infection. Issue 5 (4th May 2017) - White, P. Lewis; Backx, Matthijs; Barnes, Rosemary A.
ABSTRACT: Introduction : Pneumocystis jirovecii is a ubiquitous fungus, which causes pneumonia in humans. Diagnosis was hampered by the inability to culture the organism, and based on microscopic examination of respiratory samples or clinical presentation. New assays can assist in the diagnosis and even aid with the emergence of resistant infections. Areas covered : This manuscript will provide background information on Pneumocystis pneumonia (PcP). Diagnosis, from radiological to non-microbiological (e.g. Lactate dehydrogenase) and microbiological investigations (Microscopy, PCR, β-D-Glucan) will be discussed. Recommendations on prophylactic and therapeutic management will be covered. Expert commentary : PcP diagnosis using microscopy is far from optimal and false negatives will occur. With an incidence of 1% or less, the pre-test probability of not having PcP is 99% and testing is suited to excluding disease. Microscopy provides a high degree of diagnostic confidence but it is not infallible, and its lower sensitivity limits its application. Newer diagnostics (PCR, β-D-Glucan) can aid management and improve performance when testing less invasive specimens, such as upper respiratory samples or blood, alleviating clinical pressure. Combination testing may allow PcP to be both diagnosed and excluded, and molecular testing can assist in the detection of emerging resistant PcP.